Climate change risk and vulnerability mapping and profiling at local level using the Household Economy Approach (HEA) - Nhamo, L.; Chilonda, Pius (OMICS Publishing Group, 2012)
The increasing frequency of extreme climate events such as droughts and floods, as well as increasing temperatures and declining rainfall, are the expected future weather patterns of climate change hot spots such as Sub-Saharan Africa. Climate change and variability hot spot areas will be most vulnerable to diminishing crop production and water resources as most people in these areas depend on rainfed agriculture for their livelihoods.While much of climate change studies have been done at global scale, the impacts of climate change and variability will be felt locally at community level. In most cases adaptation occurs at local level in ways that are usually unnoticed and unaided by national governments or international organisations. This study down-scales the vulnerability of and adaptive capacity to climate change and variability to local level applying the Household Economy Approach. The focus is on local dimensions of climate change impact on water and agriculture in Western Zambia. A climate change vulnerability zone map is delineated using GIS, and a detailed profile of the zones is presented. The focus is on how communities cope with comparable climate change risks that occur today, like droughts, floods and pests, and then gauge their capacity to mitigate future CC shocks. Some adaptive measures that can be adopted to mitigate climate change impacts are recommended. The results equip policy makers with information on the impacts of climate change at local level, and capacitate them with a tool to make informed intervention.